Study of scalable vector graphics in a data environment. - Woo Chee Keen (2008)
SVG, a W3C data-driven graphics recommendation, has a versatile deployment base. This dissertation explores and discusses the implementation, integration, database interfacing and GUI issues in the development of a Web-based SVG application in a data environment. A system using SVG, HTML, PHP and MySQL was implemented and evaluated in this study.